2012
DOI: 10.1128/jcm.05556-11
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Microcalorimetric Method for Determining Drug Susceptibility in Mycobacterium Species

Abstract: Mycobacterium tuberculosis is a global public health concern, particularly with the emergence of drug-resistant strains. Immediate identification of drug-resistant strains is crucial to administering appropriate treatment before the bacteria are allowed to spread. However, developing countries, which are most affected by drug resistance, are struggling to combat the disease without the facilities or funds for expensive diagnostics. Recent studies have emphasized the suitability of isothermal microcalorimetry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
(48 reference statements)
1
33
0
Order By: Relevance
“…10 Microorganims exposed to bacteriostatic agents will mostly result in a lower heat production rate and microorganisms exposed to bactericidal agent will mostly result in a delayed heatflow pattern since a fraction of the inoculum is killed. 14,15 There are several limitations of the present study. Firstly, there is no golden-standard of implant-related infections.…”
Section: Discussionmentioning
confidence: 91%
“…10 Microorganims exposed to bacteriostatic agents will mostly result in a lower heat production rate and microorganisms exposed to bactericidal agent will mostly result in a delayed heatflow pattern since a fraction of the inoculum is killed. 14,15 There are several limitations of the present study. Firstly, there is no golden-standard of implant-related infections.…”
Section: Discussionmentioning
confidence: 91%
“…3,[16][17][18][19] As only heat production is measured by a peltier element placed between the sample container and the heat sink, solid sample can be analyzed easily. Indeed, previous studies have shown that growth and antimicrobial activity could be determined accurately in solid medium using IMC 20,21 or gels. 22 In this study, we describe the use of IMC to monitor and compare the growth of bacteria at the surface and within pores of silver doped hydroxyapatite (HA-Ag) and calcium hydroxide coatings and quantify the antibacterial activity of such coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal microcalorimetry refers to heat measurement under a constant temperature, which has high sensitivity (in the microwatt range) and allows real-time monitoring of heat production (24). In several studies, microcalorimetry was used to study the metabolic activities and drug susceptibilities of bacteria, mycobacteria, pro-tozoa, schistosomas, and fungi (yeasts and molds) (25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%